(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The Programme for International Student Assessment (PISA) provides a theoretical foundation for enhancing primary school science education through inquiry-based learning, critical thinking, and contextual teaching. Integrating PISA methodologies fosters scientific literacy by encouraging problem-solving, collaboration, and real-world application of scientific concepts. This paper explores how primary educators can implement PISA’s principles to improve student engagement and academic outcomes. It highlights the role of technology, assessment-driven instruction, and cultural inclusivity in fostering effective science learning. Aligning primary education with PISA’s theoretical framework prepares students for future academic challenges and equips them with essential scientific competencies for lifelong learning.